The informal social support for autonomy and dependence in pain inventory Spanish version - Esteve-Zarazaga, Rosa; Bernardes, Sonia F.; López-Martínez, Alicia Eva; Martín-Delgado, Carmen Estela; Ramírez-Maestre, María del Carmen (Wiley, 2021)
Social support plays a crucial role in the quality of life of people with chronic pain. The Informal Social Support for Autonomy and Dependence in Pain Inventory assesses two functions of received social support: the promotion of autonomy and the promotion of dependence. The aim of this cross-sectional study was to adapt this instrument for its use in the Spanish population. The sample comprised 256 individuals with chronic pain. Participants were recruited through two local associations of people with fibromyalgia, a physiotherapy unit and a hospital pain unit. The data were collected in Spain between October 2018 and January 2020. The structure of the questionnaire was analysed using confirmatory factor analysis, average variance extracted, composite reliability and internal consistency indexes, and inter-correlations between the scales. The criterion-related validity of the instrument was analysed by investigating its relationship with pain intensity, positive and negative affect, daily functioning, activity impairment, wellbeing and satisfaction with life. The structure with the best fit had four related factors: emotional social support for the promotion of autonomy; instrumental social support for the promotion of autonomy; emotional social support for the promotion of dependence and instrumental social support for the promotion of dependence. The scales showed adequate internal consistency. An association was found between higher levels of instrumental social support for the promotion of dependence and higher levels of pain-related disability and decreased daily functioning. An association was also found between the promotion of autonomy and increased satisfaction with life. The Spanish version of the inventory shows appropriate psychometric properties. In the setting of disability prevention, this instrument is useful in assessing the support relationships between people with chronic pain and their relatives.
Keywords: Dolor - Aspectos psicológicos; Trabajo social; Enfermos - Aspectos psicológicos; Autonomía (Psicología); Activities of daily living; Chronic pain; Emotional adjustment; Functional autonomy; Psychometric properties; Social support; Validation study